Training and competency frameworks used in the preparation of healthcare professionals for head and neck cancer screening: A scoping review protocol - Louise C. Occomore-Kent; Charitini Stavropoulou; Elizabeth C. Ward; Chris Elkington; John C. Hardman; Joanne M. Patterson; Nikki Rousseau; Vinidh Paleri; Madeline Cruice (PLoS ONE, 2025)
Objectives This scoping review aims to identify existing training and competency frameworks for healthcare professionals who assess or screen patients on the suspected Head and Neck Cancer (HNC) pathway or in extended practice models, and to explore how skills are developed, and competence assessed, prior to practice. Introduction Up to 97% of people referred with suspected HNC in the UK do not have cancer. This contributes to long wait lists and referral to treatment time in HNC services. A potential solution is for Speech and Language Therapists (SLTs) to assist such services by screening low-risk patients, specifically those presenting with hoarseness or oral-pharyngeal dysphagia. If SLTs are to screen low-risk patients safely and effectively, then specific training and competencies are required. Inclusion criteria International sources written in English between 2014–2025 that involve training and competencies for healthcare professionals who assess or screen patients for HNC. Methods The protocol presents the scoping review process that will be undertaken, which will be conducted as per the Joanna Briggs Institute Manual for Evidence Synthesis and reported in accordance with PRISMA-ScR guidance. Five databases and grey literature will be searched using a peer-reviewed search strategy. Professional organisations will be contacted for unpublished tools from clinical practice. Titles and abstracts will be screened using an a priori protocol. Eligible sources will be charted using an a priori framework and will undergo deductive content analysis. Results will be reported quantitatively and qualitatively using flow charts, tables and visual representations to outline the process and present the results.